Rent-seeking a selective survey of recent literature. - Rajagopalan, R. (1996)
"In this article, the author reviews some of the recent literature on rent-seeking and points out the relevance of the insights of the literature for the on-going policy debates on economic reforms."
Keywords: Rent - India; India - Economic policy; Economic planning and administration